Ratio of Vascular Pedicle Width and Thoracic Diameter to Differentiate Cardiogenic and Non-Cardiogenic Pulmonary Edema - Rahmi Afifi; Achmad Fachri; Amir Sjarifuddin Madjid; Joedo Prihartono; Marcel Prasetyo; Andreas Christian (Makara Journal of Health Research, 2022)
Background: Excess intravascular volume evaluation is essential in the intensive care unit (ICU); however, clinical information to differentiate cardiogenic and non-cardiogenic pulmonary edema has been proven ineffective. Thus, this study aimed to distinguish cardiogenic from non-cardiogenic pulmonary edema using the ratio of vascular pedicle width (VPW) to thoracic diameter (VPTR).